2015
DOI: 10.1099/jmm.0.000090
|View full text |Cite
|
Sign up to set email alerts
|

Limited genetic diversity and extensive antimicrobial resistance in clinical isolates of Acinetobacter baumannii in north-east Iran

Abstract: This study determined the mechanisms and patterns of antimicrobial resistance among the isolates obtained from different wards of a teaching hospital in the city of Mashhad in north-east Iran. Between January 2012 and the end of June 2012, 36 isolates of Acinetobacter baumannii were collected from different wards of Ghaem Hospital. Antimicrobial susceptibility testing and epsilometer testing (E-test) were performed. The genetic resistance determinants of A, B and D classes of b-lactamases, aminoglycoside modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
7
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
8
7
1
Order By: Relevance
“…Our results are also in agreement with a previous study by Farsiani et al [18] in 2015 who reported that the tetA gene was not found in any of the strains whereas tetB was detected in 100% of the strains. In our study, the increased level of resistance to tetracyclines was observed in spite of any detectable differences in prevalence of tetA and tetB in all of the isolates.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are also in agreement with a previous study by Farsiani et al [18] in 2015 who reported that the tetA gene was not found in any of the strains whereas tetB was detected in 100% of the strains. In our study, the increased level of resistance to tetracyclines was observed in spite of any detectable differences in prevalence of tetA and tetB in all of the isolates.…”
Section: Discussionsupporting
confidence: 94%
“…Our results indicated that all A. baumannii isolates were MDR and carbapenem resistant. The high prevalence of MDR A. baumannii strains is in accordance with the findings reported by Farsiani et al (97%) and Rynga et al (85%) in Iran and India, respectively [20], [21]. The global spread of MDR clones in healthcare settings has raised a great deal of concern, because carbapenem agents are commonly the first choice in the treatment of A. baumannii infections [22], [23].…”
Section: Discussionsupporting
confidence: 85%
“…A study from China has reported the occurrence of tetA and tetB as 26.5% and 65.3% respectively [33]. A recent study from Iran has reported that tetA was not found and all 35 tetracycline-resistant A. baumannii isolates were found to possess the tetB gene [34]. Most of the trimethoprim-sulfamethoxazole resistant strains in this study i.e.…”
Section: Discussionmentioning
confidence: 45%